Output, prices, and the distribution of consumption in rural India - Bell, Clive; Klonner, Stefan (Agricultural economics, 2005)
This paper analyzes the relation among agricultural output, inflation and the distribution of consumption in rural India, using the Singh-Maddala family to model the entire distribution parametrically. Employing a benchmark case in which growth is distributionally neutral and idiosyncratic shocks are completely smoothed, and using a GMM-estimator to deal with potential simultaneity between output and consumption, we conclude that: (i) growth was not distributionally neutral; (ii) good harvests (relative to trend) yielded improvements according to first-order stochastic dominance; (iii) slow growth before 1980 went with decreasing inequality; (iv) accelerated growth thereafter tended to increase inequality, though yielding improvements according to first-order stochastic dominance; (v) consumption-smoothing was incomplete.